Ammonia-n removal by using soil water-optimization - Nurul Nadia, Mior Rahim (2014)
Ammonia-N occurs naturally and is produced by human activity. It is an important source of nitrogen which is needed by plants and animals. Bacteria found in the intestines can produce ammonia-N. In the poultry farm, ammonia-N can be found the chicken‟s manure, where in the high concentration of ammonia-N can cause health effect to the poultry. This is because ammonia-N was a strong colorless gas that can poison the respiratory system if exposed to the gas for a long period and in high concentration. Therefore, a solution must be studied to reduce the ammonia-N‟s concentration in the poultry farm. There are plenty of studies done to reduce the ammonia-N‟s concentration by the researchers. Soil water culture will be the best treatment since it is simple and the cost to do the treatment is cheaper than other treatments existed. There are several microorganisms that can be found in the soil mixed culture that are Nitrosomonas sp., Nitrobacter sp, Nitrosolobus sp., Nitrospira sp, and Nitrovibrio sp.. These microorganisms are important for nitrification process where ammonia-N‟s concentration will be reduced. Two parameters will be considered in these treatments, which are soil mixed culture to water ratio and the temperature during the treatment. In this study, it was aiming to optimize the parameters for the reduction of ammonia-N‟s concentration by using microorganism found in soil mixed culture. This study using optimization method, where a few combination of parameter were used to obtain the best process input values. For soil mixed culture, ratio of 1:4, 1:5, 1:6, 1:7 and 1:8 were used, while for temperature, range between 25°C to 35°C were used in the experiment. Soil mixed culture was mixed with ammonia-N solution at the best condition to reduce the ammonia-N‟s concentration by using nitrification process. The mixture of ammonia-N and soil mixed culture were incubated for about 3 hours. The concentration of the mixture was measured by using spectrophotometer. Based on 13 experimental runs, the experiment was proceed to the validation run where temperature of 27.5°C and 32.5°C and soil to water ratio of 1:5 and 1:7 were used to know the experiment error to choose the best parameters for ammonia-N removal. The best condition for the highest ammonia-N removal that was 57% were at temperature of 32.5°C and soil mixed culture of ratio 1:5 with the experiment error of 9.195%. Since the result obtained showed that ammonia-N concentrations were closed to theoretical value using RSM, this can proved that RSM analysis was a useful technique for optimizing the nitrification of ammonia-N. From this study, the research can be furthered by testing the effect of pH on the nitrification process since nitrification also effected by pH value of soil mixed culture